The Influence of the Quality of Human Resources, Operator Training and Work Facilities on the Effectiveness of the Village Financial System in Banjarnegara - Faris, Fibriansyah M; Yanuar, Restianto; Wita, Ramadhanti (Monas: Jurnal Inovasi Aparatur, 2024)
This research aims to assess the influence of the quality of human resources, operator training, and work facilities on the effectiveness of the use of Siskeudes in village government. The Siskeudes application is run by operators, namely village officials/village officials who have participated in training activities. There are obstacles in using the Siskeudes application, such as the quality of human resources which are not yet optimally qualified in relation to the use of technology, facilities which are not updated and up to date, and a lack of training to run and understand the Siskeudes application. The research method used was quantitative. Data collected through questionnaires that were distributed to Siskeudes operators in villages in Banjarnegara regency with a sample of 100 villages. The results of the research show that the quality of human resources has a positive and significant effect on the effectiveness of using Siskeudes. Training does not have a positive and significant effect on the effectiveness of using Siskeudes. Work facilities have a positive and significant effect on the effectiveness of using Siskeudes. The government needs to improve the quality of human resources for village officials by holding intensive training on the use of Siskeudes, and adding or updating existing work facilities to maximize the operation of the Siskeudes.